THE DESIGN OF ONLINE SMART APPLICATION SIRISKA (WORK RISK MAPPING SYSTEM): A STUDY OF OIL PALM HARVESTING WORKERS IN PTPN IV ADOLINA PLANTATION - Umi Salmah; Sri Malem Indirawati; Risanti FR Situmorang; Pauzi Ibrahim Nainggolan; Dimas Aditya Syahputra (Yayasan Education and Social Center, 2023)
Background: National Social Security Agency for Employment (BPJS Ketenagakerjaan) in North Sumatra has noted since January 2021 there were 1,272 work accident cases in North Sumatra. Work accident prevention data with a scientific approach already has adequate information, but the digitalization era 4.0 prioritizes fast availability of information, where all entities in the industrial environment are always connected and can share information with each other. By using fast information it will make it easier for decision maker to make faster decisions and control actions in work safety and health issues. Method: The type of research was the System Development Life Cycle (SDLC) method in 9 afdelings with a total of 219 oil palm harvesters. Results: This application is the final process of the research, namely evaluating the results of the test and the feasibility of implementing the application for use by workers. Conclusion: This Android-based application can help map the risks of near misses and work accidents, making it easier for companies to record data on near misses and work accidents. In addition, the data input process by workers can be carried out quickly because the data input is done in real time